The New Testament speaks ; v. 2 God's Word for a former generation explained for today's people - Fleming, Donald C. (Kowloon, Hong Kong Living Books for All, 1981)
Contents : v. 2 : The New Testament world, Acts, The Post-Acts period.
Brethren writer. Donated by the author.
Keywords: Bible. N.T. -- introductions